Amber alert [videorecording (DVD)] - Bellessa, Kerry; Oram, Joshua; Oram, Joshua; Panettiere, Hayden; Williams, Tyler James, 1992-; Dunn, Kevin, 1956-; Miggs, Don; Bazeli, Luka; Wegert, Sally Jean; Morgan, Molly (Costume designer) (Lionsgate, 2025)
A ride-share turns into a high-stakes game of cat and mouse after it follows a car fitting the description of an AMBER ALERT.